THE INFLUENCE OF SWITCHING COST, TIME AND VARIETY SEEKING ON CONSUMER SWITCHING INTENTION (A STUDY ON KIOSK AND MINIMARKET IN NORTH MINAHASA) - Rumengan, Rosaline L. (Jurnal Berkala Ilmiah Efisiensi, 2015)
ABSTRACT There are some factors on consumer switching intention such as switching cost, time, and variety seeking. This research aims to analyze switching cost, time, and variety seeking on consumer switching intention at stalls and conveniance stores simultaneously or partialy, The respondents which were the customers who have experienced making shopping transaction at stall and convenience store. Samples were taken from 100 peopel. The analysis used is multiple linear regressions. The results showed switching cost significant influence on consumer switching intention simultaneously but not partialy, time and variety seeking are significant influence on consumer switching intention simultaneously and partialy. Variety seeking as the dominant influence compare with the other variables that influence on Consumer Switching Intention. Keywords: Switching Cost, Time, Variety Seeking, Switching Intention